Female in board and earnings management: Evidence in Indonesia non-financial firms - Sofian Sofian; S, Patricia Febrina Dwijayanti; Hendra Wijaya (University of Merdeka Malang, 2020)
The purpose of this study is to analyze the effect of females on the board on earnings management in Indonesia's Non-Financial Firms. Females on the board comprise of females in the board of commissioners, females in the board of directors, and females in the audit committee. This study also breakdown the full sample into small, medium, and large firms. The sample of this study consists of 291 non-financial firms listed in the Indonesia Stock Exchange over the period 2015-2017. This study measures earnings management using discretionary accruals. The data were analyzed using panel data regression. This study found that females in the board of commissioners, females in the board of directors, and females in the audit committee do not affect earnings management. This study also found that females in the board of directors in small firms have a positive effect on earnings management and have a negative effect on medium firms. This study contributes to the role of females in corporate governance in Indonesia's non-financial firms to reduce earnings management. JEL Classification: G34, M41DOI: https://doi.org/10.26905/jkdp.v24i4.4230